Methods for the integration of multi-omics data: mathematical aspects. Issue 2 (February 2016) - Bersanelli, Matteo; Mosca, Ettore; Remondini, Daniel; Giampieri, Enrico; Sala, Claudia; Castellani, Gastone; Milanesi, Luciano
Abstract Background Methods for the integrative analysis of multi-omics data are required to draw a more complete and accurate picture of the dynamics of molecular systems. The complexity of biological systems, the technological limits, the large number of biological variables and the relatively low number of biological samples make the analysis of multi-omics datasets a non-trivial problem. Results and Conclusions We review the most advanced strategies for integrating multi-omics datasets, focusing on mathematical and methodological aspects.